Tonic hyper‐connectivity of reward neurocircuitry in obese children. (25th March 2014) - Black, William R.; Lepping, Rebecca J.; Bruce, Amanda S.; Powell, Joshua N.; Bruce, Jared M.; Martin, Laura E.; Davis, Ann M.; Brooks, William M.; Savage, Cary R.; Simmons, W. Kyle
<x xml:space="preserve">Abstract</x> Objective Obese children demonstrate less activation in prefrontal regions associated with self‐control and inhibition when presented with food cues and advertisements. This study evaluates the differences between obese and healthy weight children in resting‐state functional connectivity to these brain regions. Methods Seed regions in bilateral middle frontal gyri were chosen based on previous task‐based analysis showing differences between obese and healthy weight children's responses to food‐associated stimuli. Functional connectivity to these seed regions was measured in resting‐state scans collected in obese and lean children undergoing fMRI. Results Obese children exhibited greater resting‐state functional connectivity than healthy weight children between the left middle frontal gyrus and reward‐related regions in the left ventromedial prefrontal cortex, as well as the left lateral OFC. Conclusion Previously published results demonstrated that obese children exhibit less activity in brain regions associated with self‐control when viewing motivationally salient food advertisements. Here, it is shown that the obese children also have tonically greater input to these self‐control regions from reward neurocircuitry. The greater functional connectivity between reward and self‐control regions, in conjunction with weaker activation of self‐control neurocircuitry, may render these children more susceptible to food advertisements, placing them at elevated risk for over‐feeding and obesity.